Copper(II) chemistry of the functionalized macrocycle cyclam tetrapropionic acid - Comba, Peter; Jakob, Maik; Morgen, Michael (Dalton transactions, 2013)
The CuII complex of H4TETP (H4TETP = 1,4,8,11-tetraazatetradecane-1,4,8,11-tetrapropionic acid) is five-coordinate with a distorted square-pyramidal structure (τ = 0.45; i.e. the geometry is nearly half-way between square-pyramidal and trigonal-bipyramidal) and a relatively long Cu-N and a short Cu-O bond; the comparison between powder and solution electronic spectroscopy, the frozen solution EPR spectrum and ligand-field-based calculations (angular overlap model, AOM) indicate that the solution and solid state structures are very similar, i.e. the complex has a relatively low “in-plane” and a significant axial ligand field with a dx2−y2 ground state. The ligand-enforced structure is therefore shown to lead to a partially quenched Jahn-Teller distortion and to a relatively low complex stability, lower than with the corresponding acetate-derived ligand H4TETA. This is confirmed by potentiometric titration and by the biodistribution with 64Cu-labeled ligands which show that the uptake in the liver is significantly increased with the H4TETP-based system.